Methane isotopic signature of gas bubbles in permafrost winter lake ice: a tool for quantifying variable oxidation levels - Sapart, Célia; Boereboom, Thierry; Röckmann, Thomas; Tison, Jean-Louis (2012)
info:eu-repo/semantics/published